1997
DOI: 10.1017/s0268416097002981
|View full text |Cite
|
Sign up to set email alerts
|

Migration, family structure and pauper lunacy in Victorian England: admissions to the Devon County Pauper Lunatic Asylum, 1845–1900

Abstract: The lunatic asylum remains one of the most remarkable institutional monuments of the modern world, dominating the social landscape of Victorian Britain and exercising a powerful attraction for social historians of medicine, an attraction almost as great as the spectre of the madhouse for contemporary novelists. Our image of the Victorian asylum is still pervaded to a surprising degree by the gloomy spectacle of the total institution presented by Michel Foucault, though it has been modified by a who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…In a pioneering work from 1855, Jarvis finds that poverty was associated with lunacy in Massachusetts, suggesting that lunacy causes poverty [25]. Similar associations are found for incarceration rates at 19th-century British asylums [9,26,27]. In the 1930s, Faris and Dunham found an ecological connection in Chicago, according to which people from poor neighbourhoods ran higher risks of hospitalisation than others [28].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a pioneering work from 1855, Jarvis finds that poverty was associated with lunacy in Massachusetts, suggesting that lunacy causes poverty [25]. Similar associations are found for incarceration rates at 19th-century British asylums [9,26,27]. In the 1930s, Faris and Dunham found an ecological connection in Chicago, according to which people from poor neighbourhoods ran higher risks of hospitalisation than others [28].…”
Section: Introductionmentioning
confidence: 88%
“…Due to the longitudinal design, our findings imply that the social causation mechanism did not contribute to the inverse relationship until the 1940s, in the sample population. Previous research on historical populations using treated samples show the expected inverse relationship [9,[25][26][27][28]. These conflicting results suggest that downward social drift had a greater impact on SES inequalities in mental health in the 19th-century than social causation mechanisms.…”
Section: Plos Onementioning
confidence: 95%
“…However, the findings of empirical studies have been mixed. Adair et al (1997) found an association between lunacy and strong family ties, and also with low mobility of populations, which is characterized by rural contexts and traditional extended, strong family systems. Miller (2007) shows that, in the second half of the nineteenth century, areas of England with higher levels of industrialization and assumed weaker family ties did not have higher rates of insanity, and instead the trend was in the reverse direction.…”
Section: Introductionmentioning
confidence: 98%
“…The increased dependency on wage labour made the labour market more competitive, and meant that more and more individuals with limited working abilities had no support (Scull, 1979). The reliance on wages and a trend towards family nuclearization were also expected to reduce the practical possibilities of families taking care of mentally-ill relatives (Adair et al, 1997; Baur, 2013; Miller, 2007; Walton, 1979; Wright, 1998). Thus, the growth of institutions can be seen as a response to increased demand for care (Wright, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…10 More recently, the impact of migration, internal and transnational, on these institutions has also attracted serious historical study. 11 Much of this work has focused on North America and the Antipodes, contexts which were notable for the high proportion of Irish admissions. 12 In mid-nineteenth-century Newfoundland, for example, Irish-born migrants made up over 40 per cent of the intake to a provisional asylum set up to cope with the sudden rise in mental illness; in Nova Scotia asylum Irish-born patients constituted 19 per cent of admissions even though they only accounted for 3 per cent of the general population.…”
mentioning
confidence: 99%